Induction of mutations and plant biotechnology to produce stress-resistant crops with higher yields - Barriento-Alfaro, Frank (2024)
Mutations and the genetic variability caused by them play a fundamental role in the genetic improvement of plants. Mutation induction or mutagenesis represents a rapid and effective option for the development of new varieties that maintain optimal productivity levels in challenging agricultural environments. Mutation induction can be carried out using physical agents, chemical agents, or gene editing tools. The combined use of mutagenesis with in vitro tissue culture techniques allows for the establishment of efficient and cost-effective selection strategies. This article provides a brief overview of mutation induction, the most commonly used techniques for this purpose, and some improvements achieved in various crops in relation to biotic stress, abiotic stress, and productive yield. Finally, it examines the historical landscape of genetic improvement through mutation induction in Costa Rica, specifically in the crops of greatest economic and social relevance to the country.